Desain Dan Implementasi Transformator Satu-Fasa Dry-Type Dengan Pendekatan Core Geometry - Saputra, Masramdhani; Santoso, Asfari Hariz; Ridzki, Imron; Wiwaha, Sigit Setya; Anindyasani, Erlinda (Elposys: Jurnal Sistem Kelistrikan, 2023)
Energy is one of the most important needs for humans to support daily life, especially for developing countries such as Indonesia. One of the energies needed in human life is electrical energy. For this reason, innovation was developed, namely a dry-type Single-Phase Transformer with a core geometry approach developed in the AL 1.01 building of the State Polytechnic of Malang. Calculations performed on the tool are to calculate the value of windings per volt (GPV) and the number of primary and secondary windings. Its manufacture uses a toroid-shaped transformer core. The core specification of the transformer is an outer diameter of 15cm, then an inner diameter of 5.8 cm, and a height of 7cm. The toroid transformer core that will be used is previously isolated from the transformer first to avoid leakage current which can cause heat in the transformer core. The density of the email wire from the transformer winding both from the primary and secondary windings will affect the performance of the transformer, the more tightly the email Wire is wrapped in the transformer core, the vibration generated from the transformer will be smaller, this will affect the voltage losses later in the transformer testing phase carried out using different beaban, each load changes the efficiency of the transformer that has been made will also change, this is because each load tested has different factors.